2018
DOI: 10.1248/bpb.b17-00589
|View full text |Cite
|
Sign up to set email alerts
|

Differential Development of Facial and Hind Paw Allodynia in a Nitroglycerin-Induced Mouse Model of Chronic Migraine: Role of Capsaicin Sensitive Primary Afferents

Abstract: Despite the relatively high prevalence of migraine or headache, the pathophysiological mechanisms triggering headache-associated peripheral hypersensitivities, are unknown. Since nitric oxide (NO) is well known as a causative factor in the pathogenesis of migraine or migraine-associated hypersensitivities, a mouse model has been established using systemic administration of the NO donor, nitroglycerin (NTG). Here we tried to investigate the time course development of facial or hindpaw hypersensitivity after rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…NTG-induced migraine is related to its metabolite NO; therefore, the sGC stimulator VL-102 can replace NTG in the model [36]. In addition, Sol-Ji Kim reported the opposite result, which may be related to selecting different facial area; he tested whisker pads rather than periorbital area [37]. In addition to headache, CM patients may experience hyperalgesia of extracephalic areas, which is an outward manifestation of central sensitization [4, 38].…”
Section: Discussionmentioning
confidence: 99%
“…NTG-induced migraine is related to its metabolite NO; therefore, the sGC stimulator VL-102 can replace NTG in the model [36]. In addition, Sol-Ji Kim reported the opposite result, which may be related to selecting different facial area; he tested whisker pads rather than periorbital area [37]. In addition to headache, CM patients may experience hyperalgesia of extracephalic areas, which is an outward manifestation of central sensitization [4, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, NTG administration increased acetone sensitivity in the forehead only in nasociliary nerve ligated side [46]. In a NTG-induced mouse model of chronic migraine, the duration of withdrawal responses to acetone in the facial region were significantly increased in mice treated with NTG compared to control [52]. Alvarez et al showed an enhanced response to acetone in neuropathic mice in their model for posttraumatic trigeminal neuropathic pain [53].…”
Section: Sensory-discriminative Aspectsmentioning
confidence: 99%
“…For example, Brennan et al showed that a higher dose of nitroglycerin was required to elicit differences in thermal allodynic responses in transgenic mice compared to a lower dose required for mechanical sensation [85]. In addition, Kim et al showed differential mechanical and thermal sensitivities in the orofacial region and hind paw following chronic nitroglycerin [174]. In this study, cold was assessed on the face via acetone, while heat on the paw, likely due to the difficulty to direct a thermal stimulus to the orofacial region of an awake, freely moving animal.…”
Section: Experimental Readouts: Behavioral Assaysmentioning
confidence: 99%